Das Symbolische, das Imaginäre und das Reale: Lacans drei Ordnungen als erkenntnistheoretisches Modell - Wörler, Frank (transcript, 2015)
This study evinces the relevance of Lacan's three orders, both within and without the scope of psychoanalytic doctrine: the symbolic, the imaginary and the real thus become to be seen as epistemological registers.